2017
DOI: 10.1038/mi.2016.71
|View full text |Cite
|
Sign up to set email alerts
|

Agglutination by anti-capsular polysaccharide antibody is associated with protection against experimental human pneumococcal carriage

Abstract: The ability of pneumococcal conjugate vaccine (PCV) to decrease transmission by blocking the acquisition of colonization has been attributed to herd immunity. We describe the role of mucosal IgG to capsular polysaccharide (CPS) in mediating protection from carriage, translating our findings from a murine model to humans. We used a flow-cytometric assay to quantify antibody-mediated agglutination demonstrating that hyperimmune sera generated against an unencapsulated mutant was poorly agglutinating. Passive imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 31 publications
6
94
3
2
Order By: Relevance
“…In mice, passive transfer of antibodies leads to agglutination of bacteria following an intranasal challenge, which causes the bacteria to clump and become more vulnerable to mucociliary clearance (48). Pneumococcal antibody-mediated agglutination has also been demonstrated in humans following vaccination with pneumococcal conjugate vaccine (PCV) (49). In that study, naturally acquired antibodies were present in the nasopharynx prior to vaccination but not at levels sufficient to induce agglutination.…”
Section: Clearance Of Colonization Is a Complex Processmentioning
confidence: 76%
See 1 more Smart Citation
“…In mice, passive transfer of antibodies leads to agglutination of bacteria following an intranasal challenge, which causes the bacteria to clump and become more vulnerable to mucociliary clearance (48). Pneumococcal antibody-mediated agglutination has also been demonstrated in humans following vaccination with pneumococcal conjugate vaccine (PCV) (49). In that study, naturally acquired antibodies were present in the nasopharynx prior to vaccination but not at levels sufficient to induce agglutination.…”
Section: Clearance Of Colonization Is a Complex Processmentioning
confidence: 76%
“…In young adults, systemic immunization with PCV13 leads to high concentrations of antipneumococcal IgG in serum, which spills over into the nasal mucosal compartment and can, by virtue of its agglutinating properties, prevent the development of pneumococcal colonization (49). This is likely to be the mechanism for the reduction of pneumococcal colonization following infant vaccination.…”
Section: Systemic Exposure To Pneumococcal Antigens Via Vaccination Cmentioning
confidence: 99%
“…Such memory B cells can quickly differentiate into antibody-secreting plasma cells following antigen exposure. Furthermore, the effectiveness of S. pneumoniae agglutination of airway secretions after PCV vaccination correlates with protection during experimental human colonization 28 . An additional effect of immunity demonstrated in the infant mouse model is a decrease in shedding by index pups 24 .…”
Section: Transmission Of S Pneumoniaementioning
confidence: 99%
“…In this process, antibodies agglutinate bacterial cells and accelerate clearance from the nasopharyngeal mucosa [22,32]. Recently, our group observed that incubation of PspA-specific antibodies with pneumococci led to agglutination [21].…”
Section: Discussionmentioning
confidence: 99%